THE MPLEMENTATION OF JIGSAW TYPE OF COOPERATIVE LEARNING MODEL ON STATISTICS MATERIALS FOR CLASS X STUDENTS SMA NEGERI 11 BANDA ACEH - Qurrata (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2022)
In teaching and learning mathematics, students are not only expected to master concepts, principles, facts, and skills related to mathematics, but also skills to live in society, including high self-confidence, mutual respect and belonging, high social attitudes, and problem solving skills together. This study aims to determine the learning outcomes and the level of mastery of student learning, and student responses to cooperative learning with a jigsaw type. The population in this study were all class X students of SMA Negeri 11 Banda Aceh, namely as many as 217 students in the 2015/2016 school year, while the sampling in this study was carried out using a purposive sampling technique and selected in this study were students in class X-IA3, totaling 29 student. The instruments used for collecting research data are tests, observations and questionnaires. After the collected data were analyzed using the t-test statistical formula. Based on the results of data analysis, the conclusion of this study is that from the results of data processing it is found that tcount ttable, namely 14.23 1.70, then Ho is rejected and Ha is accepted, meaning that student learning outcomes between the final test and the initial test increase after the application of the learning model cooperative jigsaw type on statistics material in class X SMA Negeri 11 Banda Aceh. The percentage of students who complete, namely 82.75%, this figure shows the value of classical student completeness is complete, namely 80%. This is according to classical completeness achieved when at least 80% of the students in the class achieve a completeness score and the student's response to learning statistics material through learning the jigsaw type cooperative model in class X-IA3 students of SMA Negeri 11 Banda Aceh is of very positive value.Keywords: Application, Cooperative Learning, Jigsaw Type Learning, and Statistics.